2020
DOI: 10.1111/bre.12456
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the evaporite accumulation and salt structures dynamics in Tiddlybanken Basin, southeastern Norwegian Barents Sea

Abstract: An extensive, reprocessed two‐dimensional (2D) seismic data set was utilized together with available well data to study the Tiddlybanken Basin in the southeastern Norwegian Barents Sea, which is revealed to be an excellent example of base salt rift structures, evaporite accumulations and evolution of salt structures. Late Devonian–early Carboniferous NE‐SW regional extensional stress affected the study area and gave rise to three half‐grabens that are separated by a NW‐SE to NNW‐SSE trending horst and an affil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Finnmark Platform, the prominent Timanian structure (T5 anomaly) creates a platform between the NW-SE oriented graben G4 related to Tiddlybanken Basin and the CNB segment (Figure 11; Hassaan et al, 2020). Recently, Hassaan et al (2021) suggested a basement-involved, arcuate horst related to the pre-existing Timanian basement grain that could be the prolongation of the deep structure represented by the T5 magnetic anomaly and corresponding lineation towards the southeast (Figure 11b).…”
Section: Basement Structural Topography and Its Influence On Basin Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Finnmark Platform, the prominent Timanian structure (T5 anomaly) creates a platform between the NW-SE oriented graben G4 related to Tiddlybanken Basin and the CNB segment (Figure 11; Hassaan et al, 2020). Recently, Hassaan et al (2021) suggested a basement-involved, arcuate horst related to the pre-existing Timanian basement grain that could be the prolongation of the deep structure represented by the T5 magnetic anomaly and corresponding lineation towards the southeast (Figure 11b).…”
Section: Basement Structural Topography and Its Influence On Basin Developmentmentioning
confidence: 99%
“…The region was under warm, arid to semi-arid climate conditions due to the drift into the subtropical zone, and as a consequence, the deposition of the warm-water carbonates and sabkha evaporites of the Gipsdalen Group (Figure 3) took place (Larssen et al, 2002;Stemmerik, 2000). The effect of the younger extension was less pronounced in the southeastern Norwegian Barents Sea, and layered evaporites within the Gipsdalen Group strata (Figure 3) were accumulated in postrift conditions (Figure 12b; Hassaan et al, 2020Hassaan et al, , 2021Rowan & Lindsø, 2017). The NW-SE oriented extensional stress regime (Figure 12b) affected the regional NW-SE trending half-grabens within the proto-Nordkapp Basin (Figure 12a).…”
Section: Late Carboniferous Extensionmentioning
confidence: 99%
See 2 more Smart Citations
“…Discrete Timanian structures with characteristic WNW-ESE strikes are sub-orthogonal to the N-S-trending Caledonian grain formed during the closure of the Iapetus Ocean (Gee et al, 1994;Witt-Nilsson et al, 1998;Johansson et al, 2004;. Thus far, Timanian structures have only been identified in onshore-nearshore areas of northwestern Russia and northeastern Norway and offshore in the Russian Barents Sea and southeasternmost Norwegian Barents Sea (Barrère et al, 2009(Barrère et al, , 2011Marello et al, 2010;Gernigon et al, 2018;Hassaan et al, 2020aHassaan et al, , 2020b. Therefore, the nature of basement rocks in the northern and southwestern Norwegian Barents Sea remains debatable.…”
Section: Introductionmentioning
confidence: 99%